Ко-ко-ко! и Цап-царап!: стихи для детей / Наталья Дёмышева - Демышева Наталья Антонова (Удмуртия, 2016)
Экземпляры: ф.21 (20210622) / Инвентарный номер: 61069 / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: Д 39 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5